2012
DOI: 10.1073/pnas.1115086109
|View full text |Cite
|
Sign up to set email alerts
|

Self-incompatibility response induced by calcium increase in sperm of the ascidian Ciona intestinalis

Abstract: Many hermaphroditic organisms possess a self-incompatibility system to avoid self-fertilization. Recently, we identified the genes responsible for self-sterility in a hermaphroditic primitive chordate (ascidian), Ciona intestinalis: sperm-side polycystin 1-like receptors s-Themis-A/B and egg-side fibrinogen-like ligands on the vitelline coat (VC) v-Themis-A/B. Here, we investigated the sperm behavior and intracellular Ca 2+ concentration ([Ca 2+ ] i ) in response to self/ nonself-recognition. We found that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…As s-Themis-B contains a cation-channel domain in its C terminus, we monitored ] i imaging using Fluo-8H-AM, a cell-permeable Ca 2+ indicator. Interestingly, we found that sperm [Ca 2+ ] i rapidly and dramatically increased and was maintained at a high level in the head and fl agellar regions when sperm interacted with the self-VC but not when the sperm interacted with the nonself VC (Saito et al 2012 ). The increase in [Ca 2+ ] i was also suppressed by low-Ca 2+ seawater (Saito et al 2012 ).…”
Section: Polymorphisms Among Individuals Of S/v-themis-a and S/v-themmentioning
confidence: 64%
See 2 more Smart Citations
“…As s-Themis-B contains a cation-channel domain in its C terminus, we monitored ] i imaging using Fluo-8H-AM, a cell-permeable Ca 2+ indicator. Interestingly, we found that sperm [Ca 2+ ] i rapidly and dramatically increased and was maintained at a high level in the head and fl agellar regions when sperm interacted with the self-VC but not when the sperm interacted with the nonself VC (Saito et al 2012 ). The increase in [Ca 2+ ] i was also suppressed by low-Ca 2+ seawater (Saito et al 2012 ).…”
Section: Polymorphisms Among Individuals Of S/v-themis-a and S/v-themmentioning
confidence: 64%
“…Interestingly, we found that sperm [Ca 2+ ] i rapidly and dramatically increased and was maintained at a high level in the head and fl agellar regions when sperm interacted with the self-VC but not when the sperm interacted with the nonself VC (Saito et al 2012 ). The increase in [Ca 2+ ] i was also suppressed by low-Ca 2+ seawater (Saito et al 2012 ). These results indicate that the sperm self-recognition signal triggers [Ca 2+ ] i increase or Ca 2+ infl ux, which induces an SI response to reject self-fertilization.…”
Section: Polymorphisms Among Individuals Of S/v-themis-a and S/v-themmentioning
confidence: 64%
See 1 more Smart Citation
“…2) with stronger expression of a1C, H, and S in spermatogenic testes. Elongation factor (EF) 1 gene expression was detected at similar levels in both testes, and a spermatidspecific gene, protamine 1 (Yoshinobu et al, 1997) Darszon et al, 2006;Kirichok and Lishko, 2011), and sperm binding to the egg envelope (Saito et al, 2012). Spermatozoa possess multiple types of cation channels in the plasma membrane and Ca 2+ stores, which are critical for increasing cytoplasmic Ca 2+ in every step of sperm-egg interaction (Darszon et al, 2006;Marquez et al, 2007).…”
Section: Voltage-dependent Camentioning
confidence: 99%
“…Sperm with this waveform show cane-shaped "quiescence," which is observed by electric or mechanical stimulation of sperm fl agella in the sea urchin (Shingyoji and Takahashi 1995 ;Kambara et al 2011 ). On the self-nonself recognition of sperm and egg in Ciona , sperm show quiescence with a straight fl agellum in response to the increase in intracellular Ca 2+ (Saito et al 2012 ). The basic regulation of fl agellar waveform by Ca 2+ is thought to be performed by the specifi c activation of dynein arms, which results in the changes in fl agellar waveforms (Brokaw 1979 ;Lindemann and Goltz 1988 ).…”
mentioning
confidence: 99%